Private Savings Behaviour in Nepal: Longterm Determinants and Short-run Dynamics - Shrestha, Rajendra Prasad (NRB Economic Review, 2008)
With a view to explain the long-run and cyclical behaviour of private savings in Nepal during the period 1974-2005, the study employs an error-correctionframework. The study estimated 0.309 as marginal propensity to save with the corresponding value of 0.365 in the long-run. The estimation results reveal thatreal income, real government savings, real foreign savings, real interest rates, and labour market constraints play important roles in determining private savings in the short and long-run. The findings of the study suggest that there is a need to focus on development policy which increases productive base of the economy in order to increase income growth and reduce unemployment. It is also important to note that the real interest rates have a positive influence on the private savings and can be taken as an important policy variable in Nepal.